Direct Air Carbon Capture Using Metal-Organic Frameworks (MOFs) - Haider Ali; Duraid Uddin; Asad A. Naqvi; Umair Naeem; Nomaan Akhtar; Saqib Shams; Ali Karim (Memoria Investigaciones en Ingeniería)
Direct Air Carbon Capture (DACC) technology is used to remove CO₂ directly from the atmosphere, helping tackle climate change and excessive greenhouse gas emissions efficiently. In this study, a techno-economic analysis of DACC has been carried out, including its working mechanisms, energy needs, and costs, as well as a summary of the current research status. This research compares two leading metal-organic frameworks (MOFs) — MIL-101(Cr)-PEI-800 and mmen-Mg₂(dobpdc) — focusing on their energy consumption, CO₂ adsorption, and cost. This study investigates the performance of these MOFs in a temperature vacuum swing adsorption (TVSA) process, which cyclically varies temperature and pressure to capture CO₂ and regenerate adsorbents. Among all materials, mmen-Mg₂(dobpdc) achieves the best performance with a much higher capacity and a favourable nonlinear isotherm shape, indicating significantly improved efficiency and lower energy input. DACC systems based on advanced MOFs hold great promise for minimizing non-point source emissions and should thus be considered essential components of a climate change mitigation strategy. This study contributes to direct future research and development toward more efficient and cost-effective MOFs in DACC applications.